2010
DOI: 10.1136/sti.2010.042937
|View full text |Cite
|
Sign up to set email alerts
|

An immunofiltration device for the simultaneous detection of non-treponemal and treponemal antibodies in patients with syphilis

Abstract: These results indicate that the dual treponemal and non-treponemal assay could be used as a screen and confirmatory test for the serological diagnosis of syphilis in remote or resource-poor settings where there is a need to provide counselling and treatment at the initial consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…About 33% (11/33) of papers reported on conflicts of interest, with each having at least one conflict of interest. In four articles [16][18], the authors evaluated the diagnostic test they had manufactured themselves or contributed to its manufacturing. The role of conflict of interest as a predictor of diagnostic performance could not be explored.…”
Section: Resultsmentioning
confidence: 99%
“…About 33% (11/33) of papers reported on conflicts of interest, with each having at least one conflict of interest. In four articles [16][18], the authors evaluated the diagnostic test they had manufactured themselves or contributed to its manufacturing. The role of conflict of interest as a predictor of diagnostic performance could not be explored.…”
Section: Resultsmentioning
confidence: 99%
“…Although syphilis can easily be diagnosed with traditional and modern tests (44)(45)(46) and effectively treated with penicillin (47), the continuing high global prevalence of this infection is a strong argument for the need to deepen our knowledge of syphilis pathogenesis. Such research efforts will allow syphilis investigators to understand what mechanisms make T. pallidum such a successful pathogen able to invade virtually every bodily organ, including the placenta, and persist for the lifetime of the infected host, in spite of a robust immune response (48).…”
Section: Discussionmentioning
confidence: 99%
“…Although a POC test that detects both treponemal and nontreponemal antibodies has been developed, the detector conjugate needed refrigeration. 7 The test used in the present study can be performed with whole blood; it was developed to simultaneously detect both treponemal and nontreponemal antibodies; the device is stable at room temperature and does not require refrigeration. This study demonstrated that the sensitivity and specificity of the test are as good as the standard diagnostic tests for syphilis.…”
Section: The Diagnosis Of Sexually Transmitted Infections Including mentioning
confidence: 99%